Analisis Job Rotation Dalam Meningkatkan Keterampilan Kerja Guru di MA YPK Cijulang - Nur Aziz; Khidayat Muslim; Sahmidin (Education Management: Jurnal Manajemen Pendidikan Islam, 2024)
Job rotation is an effective method to enhance teachers’ work skills in educational institutions. This study aims to analyze the implementation of job rotation to improve teacher competency and productivity at MA YPK Cijulang. The research employs a qualitative descriptive approach with data triangulation through interviews, observations, and documentation. Findings indicate that job rotation is applied flexibly based on employee requests rather than as a mandatory policy, and it effectively enhances work skills, reduces boredom, and broadens teacher knowledge. The implementation positively impacts employee motivation and operational efficiency, making it an effective human resource management strategy in the educational context.